2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037103
|View full text |Cite
|
Sign up to set email alerts
|

Facial geometry and speech analysis for depression detection

Abstract: Depression is one of the most prevalent mental disorders, burdening many people world-wide. A system with the potential of serving as a decision support system is proposed, based on novel features extracted from facial expression geometry and speech, by interpreting non-verbal manifestations of depression. The proposed system has been tested both in gender independent and gender based modes, and with different fusion methods. The algorithms were evaluated for several combinations of parameters and classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…Potential developments of the proposed method include the inclusion of complementary features both within the audio domain and from the visual modality cf. [31,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential developments of the proposed method include the inclusion of complementary features both within the audio domain and from the visual modality cf. [31,19].…”
Section: Discussionmentioning
confidence: 99%
“…The binary classification method of Statak et al [17] assigned BDI-II scores of [0-9] to 'none-low depression' and to 'moderate-high depression', and used Geneva Minimalistic Acoustic Parameter Set features [18] for estimation of arousal level, achieving a classification accuracy of 82.5%. Pampouchidou et al [19] proposed binary categorical assessment, by considering BDI-II scores [0-13] as not-depressed, and as depressed. Using the covarep toolbox [20] for extracting speech-based DCT features, they achieved an F1-score of 0.64 for gender-based depression classification.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The results pointed out that the most accurate action unit for depression detection was AU14 (action unit related to contempt). In [2], the identification of depression was done by analysing facial landmark points. The distances between them were found out using euclidean and city block distance methods.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in the crosscultural study of Alghowinem et al [15] who focused on geometrical features derived from eye activity to achieve 81.3% classification accuracy utilizing one subset of the AVEC'13 dataset, among other datasets. Pampouchidou et al [16] reported 74.5% accuracy with the Local Curvelet Binary Patterns in Pairwise Orthogonal Planes, while Pampouchidou et al [17] employed geometrical features to achieve an F1 score of 58.6% in the single-modality (i.e., visual) approach and 72.8% when taking into account both audio and visual features.…”
Section: Categorical Depression Assessment With Avec Datasetsmentioning
confidence: 99%